2015
DOI: 10.1208/s12249-015-0421-y
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic Ionic Liquids as Ingredients of Gel-Based Dermal Formulations

Abstract: Abstract. Ionic liquids (ILs) have several properties that offer many advantages in dermal drug delivery systems. Depending on the chemical structure, ILs can be used for protection against microorganisms, to enhance skin penetration, and as a solvent. In the present work, SEPINEO™ P 600 formulations and hydroxyethylcellulose gels containing the hydrophilic ILs hexylpyridinium chloride, choline dihydrogen phosphate, and 1-ethyl-3-methylimidazolium ethyl sulfate were prepared, and the influence of the ILs on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 40 publications
(35 reference statements)
0
13
0
Order By: Relevance
“…Additionally, Rogers et al [82] recently demonstrated on synthetic membrane models that API-OSILs that contain lipophilic cations, preferably with established hydrogen bonds, exhibit an increased membrane transport as compared to API-OSILs with weaker electrostatic interactions or even traditional halide or metal salts. Finally, it is important to note that both hydrophobic and hydrophilic ionic liquids have been recently studied as penetration enhancers [16,20,83,84]. Various nanocarriers can serve as antimicrobial enhancers because they incorporate into lipid membranes or cell walls, leading to membrane or wall disruptions in both Gram-positive and Gram-negative bacteria strains [77,[85][86][87][88][89][90][91], therefore increasing the drug's efficiency.…”
Section: Studies On Resistant Bacteriamentioning
confidence: 99%
“…Additionally, Rogers et al [82] recently demonstrated on synthetic membrane models that API-OSILs that contain lipophilic cations, preferably with established hydrogen bonds, exhibit an increased membrane transport as compared to API-OSILs with weaker electrostatic interactions or even traditional halide or metal salts. Finally, it is important to note that both hydrophobic and hydrophilic ionic liquids have been recently studied as penetration enhancers [16,20,83,84]. Various nanocarriers can serve as antimicrobial enhancers because they incorporate into lipid membranes or cell walls, leading to membrane or wall disruptions in both Gram-positive and Gram-negative bacteria strains [77,[85][86][87][88][89][90][91], therefore increasing the drug's efficiency.…”
Section: Studies On Resistant Bacteriamentioning
confidence: 99%
“…However, poor drug solubility of many drugs in water and in most pharmaceutical grade solvents, used in the developed topical formulations, represents an obstacle. Hence, several efforts have been made to find ingredients that may assist in this challenge, and ionic liquids have been used for this purpose [6][7][8][9][10][11][12]. ILs are salts, with an organic cation and an inorganic or organic [21][22][23], that are liquid at temperatures below 100 °C or even at room temperature [21,24,25].…”
Section: Ionic Liquidsmentioning
confidence: 99%
“…
Recently, some studies have shown the relevance of using ionic liquids (ILs) to improve drug solubility/loading, permeation of topical drug delivery systems [6][7][8][9][10][11][12].
…”
mentioning
confidence: 99%
“…The wells were filled with samples of standard voriconazole and MBH; and samples were incubated. The antifungal activity of MBH was evaluated under strict aseptic conditions by measuring the clear rings appeared around the wells as zone of inhibition after the fourth day of incubation (Dobler et al 2016).…”
Section: In Vitro Antifungal Activitymentioning
confidence: 99%